Integrasi Media Pembelajaran Interaktif dalam Mendorong Partisipasi Aktif Peserta Didik - Sri Bulan; Muhammad Naim; Anita. S; Pina Pina; Sudarmin Sudarmin; Hasmi Hasmi (FKIP UNSULTRA, 2025)
The development of digital technology in the context of modern education has driven significant changes in the strategies, approaches, and learning media used by educators. One innovation considered effective in enhancing the learning experience is the use of interactive learning media. This literature review aims to analyze the role, benefits, and challenges of integrating interactive learning media in increasing active student participation at various levels of education. Through a review of academic articles, the latest scientific journals, and research reports during the 2018–2025 publication period, it was found that interactive learning media such as animated videos, game-based learning applications (gamification), Augmented Reality (AR), Learning Management Systems (LMS), and digital simulations can have a positive impact on student motivation, engagement, and learning outcomes. The study also shows that interactive learning can improve students' critical thinking skills, collaboration, and creativity through responsive and adaptive two-way learning activities. However, several challenges remain, such as teacher readiness, access to technology, training in digital media use, and selecting media appropriate to learning objectives. Based on the results of the literature analysis, the integration of interactive learning media is considered a relevant and strategic pedagogical solution to support active student participation, particularly in the era of technology-based learning and the Independent Curriculum.